Tumor targetable and pH-sensitive polymer nanoparticles for simultaneously improve the Type 2 Diabetes Mellitus and malignant breast cancer. Issue 4 (1st April 2022) - Tang, Shi; Wen, Peiqi; Li, Kaiheng; Deng, Jiehua; Yang, Bo
ABSTRACT: In the recent study, we have developed novel tumor targetable and pH-sensitive PLGA nanoparticles co-loaded with camptothecin (CPT) and metformin (Metf) to simultaneously improve the Type 2 Diabetes Mellitus (T2DM) and malignant breast cancer. To improve the drug loading efficiency, the hydrophobic CPT was conjugated with PLGA polymer by the pH-sensitive hydrazone bonds (hyd). Then, the Metf was physically loaded into the hydrophobicity inner core of CPT-conjugated PLGA nanocomplex to form the dual drugs-loaded nanoparticles (NP/CPT-Metf). Furthermore, on the surface of NP/CPT-Metf was modified with tumor-homing CGKRK peptides to obtain the tumor targetable and pH-sensitive polymer nanoparticles (CNP/CPT-Metf). It was demonstrated that the developed CNP/CPT-Metf displayed sufficient sensitivity to the weak acidic tumor microenvironment. Besides, excellent ability of CNP/CPT-Metf to mediate accumulation of drugs in cells and tumor tissues finally in turn resulted in a signal enhanced anti-tumor effect. Furthermore, it was demonstrated as well that CNP/CPT-Metf was able of significantly alleviating the type 2 diabetes mellitus in diabetic mice. In summary, the developed multifunctional polymer nanoparticles might represent a promising strategy for simultaneously improve the T2DM and treat malignant breast cancer. GRAPHICAL ABSTRACT: uf0001